2021
DOI: 10.3390/insects12060568
|View full text |Cite
|
Sign up to set email alerts
|

Newly Emerging Pest in China, Rhynchaenusmaculosus (Coleoptera: Curculionidae): Morphology and Molecular Identification with DNA Barcoding

Abstract: The oak flea weevil, Rhynchaenus maculosus Yang et Zhang 1991, is a newly emerging pest that severely damages oak (genus Quercus) in China. The first R. maculosus outbreak occurred in 2020 and caused spectacular damage to all oak forests in Jilin province, northeast China. The lack of key morphological characters complicates the identification of this native pest, especially in larva and pupa stages. This is problematic because quick and accurate species identification is crucial for early monitoring and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Distribution of an insect pest is one of the population properties, which is of great significance either in theoretical ecology as well as in pest monitoring and control 19 , especially for a newly-emerging pest. Our studies showed that R. maculosus , a newly-emerging insect pest in recent years 2 , is distributed locally in Northeast China, including the Liaoning, Jilin, and Heilongjiang provinces. Some leaf-mining pests in the weevil family have become invasive pests, causing economic and ecological impacts to the newly introduced areas 20 .…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Distribution of an insect pest is one of the population properties, which is of great significance either in theoretical ecology as well as in pest monitoring and control 19 , especially for a newly-emerging pest. Our studies showed that R. maculosus , a newly-emerging insect pest in recent years 2 , is distributed locally in Northeast China, including the Liaoning, Jilin, and Heilongjiang provinces. Some leaf-mining pests in the weevil family have become invasive pests, causing economic and ecological impacts to the newly introduced areas 20 .…”
Section: Discussionmentioning
confidence: 72%
“…Three oak forests over 100 km apart in each province were selected to collect the insect pests. The collection of adult samples was performed using sticky traps around the trunk combined with hand-collection from mid-April to early May each year 2 . The insect samples were taken into laboratory for species identification carried out by both morphology and molecular method.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA barcoding, a method for species identification based on standard gene markers, for example, the mitochondrial cytochrome oxidase subunit I (COI) gene for animals, has become a reliable basis for assembling reference sequence libraries of known species and discovering new species in many taxonomic groups (Hebert et al., 2003 ; Hebert et al., 2004 ). The efficacy of this approach has been successfully demonstrated across various taxa of Coleoptera, including Curculionidae (Astrin et al., 2012 ; Ma et al., 2022 ; Yang et al., 2021 ), Coccinellidae (Huang et al., 2020 ), and Tenebrionidae (Li et al., 2020 ). Previous studies have also shown the effectiveness of DNA barcoding in species identification and diagnosis within the Curculionoidea (Germann et al., 2017 ; Ma et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%